Giving aromatherapy to reduce mental workload of human resources department employees of company X - Ayu Irmawati (Psycho Holistic, 2024)
This study aims to reduce mental workload through the provision of aromatherapy to PT. X employees. Mental workload is a problem that is often experienced by employees of PT X which in the long run will affect both physical health such as the appearance of headaches, fever, and heart attacks and mental such as the emergence of anxiety, sadness, and despair. Aromatherapy is a therapeutic action that utilizes essential oils with the aim of improving a person's physical and psychological health. This study applied a quantitative approach with pre-test and post-test design. The subjects in this study were 6 people. The administration of aromatherapy was carried out for 3 days, and its effectiveness was measured using the NASA-TLX method. Based on results, there is a significant decrease of mental workload. The findings of this study have practical indications specifically for HR department employees and agencies in helping employees to reduce mental workload. By integrating the use of aromatherapy in helping to reduce the mental workload of employees in the work area, it is expected that employees can feel more relaxed and calmer when completing work.